EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KELURAHAN SUKODADI KECAMATAN SUKARAMI KOTA PALEMBANG - Destiannisa Herjayanti (STIA SATYA NEGARA PALEMBANG, 2025)
Community welfare is a benchmark for measuring the development of its citizens within a nation. TheFamily Hope Program (PKH) provides assistance in the fields of health, education, and social welfare. This study aims to determine the effectiveness of the Family Hope Program (PKH) in improving community welfare in Sukodadi Village, Sukarami District, Palembang City. The focus of this study is to determine and evaluate the extent to which this program has a positive impact on aid recipients. The method used in this research is a qualitative method with data collection techniques of interviews, observation, literature studies and documentation. The research results show that the Family Hope Program (PKH) has been effective in improving community welfare. It helps alleviate the burden and reduce poverty. However, several indicators remain ineffective. One indicator that has not reached the effective level is inaccurate program targeting. However, the PKH Support Team has made efforts, including regular data graduation to ensure that aid recipients are accurately targeted. Keywords: Effectiveness, Family Hope Program (PKH), and Community Welfare